Kinetic Parameters from TG Analysis of Co2+, Ni2+, and Cu2+ Complexes - Alam, M.M.; Sinha, H.K.; Singh, V.P. (Asian Journal of Chemistry, 2010)
Kinetics of thermal decompositions of pyridine and morpholine complexesof Co2+ , Ni2+ and Cu2+ ions have been studied. Kinetic parameters,viz., apparent activation energy, frequency factor, activation entropy andapparent order of reaction have been determined using the graphicalmethod of Freeman and Carrol and results were compared by Coats-Redfernmethod. It was found that the data by both the methods are ingood agreement.